Spatial Mapping of Sero Traditional Capture Fishery Operation Locations in Pangkep Regency Waters, South Sulawesi - Ihsan, Ihsan; Jamal, Muhammad; Asbar, Asbar (Agrikan Jurnal Agribisnis Perikanan, 2023)
The research aims 1) To examine the spatial distribution of oceanographic parameters of temperature, salinity, chlorophyll and bathymetry and 2) To determine the types of catch by traditional fishing gear. The research was conducted in June - July 2023, in the coastal waters of Pangkep Regency. The research uses a survey method. The data collected includes temperature, chlorophyll salinity and bathimetery data, through fashionable satellite imagery and direct measurements in the field. Data were analyzed using a geographic information system and analysis of fish species using the Market Fishes of Indonesia guide, (2013). The distribution of oceanographic aspects includes temperatures in June - July respectively in the temperature range 29.35-29.74?C and temperature 26.42-30.03?C and the temperature range in August is 27.22-33.39?C ; chlorophyll in July 2021 ranged from 0.1086 2.657 mgm-3. and the results of the distribution of salinity measurements in June 2021 in the range 32.96 - 34.05 and in July 2021 in the range 33.32 - 33.94 . The recommended potential area for operating sero traditional fishing gear is the priority location for sero operation with a high suitability coastal water area of 887.47 Ha and a low suitability with an area of 7,326.49 Ha. Types of catches sero fishing gear, identified 26 species of fish consisting of small pelagic fish and demersal fish including reef fish that migrate to the beach during low tide.